Palliativmedizin und Betäubungsmittelrecht Möglichkeiten und Grenzen - Duttge, Gunnar; Nauck, Friedemann; Weber, Alexandra Kristina (Universitätsverlag Göttingen, 2013)
The collection is related to a workshop at the Georg-August-University Göttingen from 2012 and refers to the use of narcotics in palliative care. Experts of law and medicine discuss the situation of doctors leaving narcotics at their patients home, the prevailing legal norms and the need for reform.